2011
DOI: 10.1111/j.1651-2227.2011.02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation in leisure activities and sensory modulation deficiencies of children with atopic dermatitis

Abstract: Children with AD may show lower preference to participate in activities in comparison with their typical peers. This lower preference may be impacted by their SMD. Multidisciplinary intervention may be beneficial for children with AD. This intervention should refer to AD symptoms and considers the child's sensory profile and participation in daily living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…Some authors suggested that children with AD tend not to participate in leisure activities at the level of their healthy counterparts . By contrast, the overall attitude of parents in our study was that their children with AD were capable of performing all activities and had no issues with making friends or participating in various school activities, indicating that AD has not been seen as stigmatic.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Some authors suggested that children with AD tend not to participate in leisure activities at the level of their healthy counterparts . By contrast, the overall attitude of parents in our study was that their children with AD were capable of performing all activities and had no issues with making friends or participating in various school activities, indicating that AD has not been seen as stigmatic.…”
Section: Discussioncontrasting
confidence: 63%
“…The average score of parental knowledge on AD in our survey was about 9.5 out of 12, with the lowest score of 6, suggesting that the parents in our study were considerably familiar with AD‐related issues. The assessment of knowledge in a study among Korean adults, children, and parents of patients showed that the highest percentage of correct answers was related to seasonal variation in AD symptoms (93.3%), relieving of AD symptoms through exfoliation by rubbing with a flannel (91.1%), that AD was a genetic disorder not related to the environment (87.9%), that mild symptoms of AD did not require therapy (79.6%), and that AD was related to allergic rhinitis and asthma (70.9%) . On the other hand, compared to percentage of least correct answers in our survey, the distribution in the survey by Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Gender is another determinant of children’s participation, as boys and girls prefer different types of activities (Engel-Yeger & Jarus, 2008; King et al, 2007). Evidence suggests a relationship exists between children’s sensory processing patterns and their level of participation in different activities (see Dunn, 2007; Engel-Yeger et al, 2011; Mische Lawson & Dunn, 2008; Welters-Davis & Mische Lawson, 2011). Studying children’s preferences in different play and leisure activities is important to enhance their participation in these activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence suggests that sensory processing patterns affect children’s participation and choices in different daily life activities (Bundy, Shia, Qi, & Miller, 2007; Dunn, 1997, 2007; Engel-Yeger, 2008; Engel-Yeger, Shani-Adir, & Kessel, 2011; Engel-Yeger & Ziv-On, 2011; Mische Lawson & Dunn, 2008). Therefore, it is important to consider children’s sensory preferences when offering play, leisure, and educational activities.…”
mentioning
confidence: 99%
“…Nevertheless, the knowledge about the ability of children with migraine to process sensory input is limited. Since sensory processing abilities have a direct impact on daily function (24) and quality of life (25), by exploring the prevalence of SPD among children with migraine and their impacts on children's quality of life, intervention programs may be more efficient. Hence, the aims of this study were: (1) Compare sensory processing abilities between children with migraine and healthy controls (2) Compare the quality of life between children with migraine and healthy controls (3) Examine the correlations between sensory processing, migraine characteristics and severity and quality of life among children with migraine (4) Examine the contribution of headache-related disability and sensory processing to the prediction of quality of life among children with migraine.…”
Section: Introductionmentioning
confidence: 99%